2010
DOI: 10.1117/12.854396
|View full text |Cite
|
Sign up to set email alerts
|

Femtosecond laser fabrication of hybrid micro-optical elements and their integration on the fiber tip

Abstract: Femtosecond laser photo-polymerization of zirconium-silicon based sol-gel photopolymer SZ2080 is used to fabricate micro-optical elements with a single and hybrid optical functions. We demonstrate photo-polymerization of the solid immersion and Fresnel lenses. Gratings can be added onto the surface of lenses. The effective refractive index of polymerized structures can be controlled via the volume fraction of polymer. We used woodpile structure with volume fraction of 0.65-0.8. Tailoring of dispersion properti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 29 publications
1
4
0
Order By: Relevance
“…Depending on the microtower layer, the surface roughness was either ∼11 or ∼31 nm due to the fluctuation of the laser dose caused by different contour geometries. The achieved surface roughness is, nevertheless, in line with previous studies; Malinauskas et al have reported a roughness of ∼30 nm ±3 nm for sol−gel photopolymer SZ2080, 61 and Takada et al found a roughness of 4 to 11 nm for urethane acrylate resin SCR500. 62 It has been suggested that the higher surface roughness resulting in an increase of the surface area can promote the attachment of glioblastoma cells.…”
Section: Discussionsupporting
confidence: 91%
“…Depending on the microtower layer, the surface roughness was either ∼11 or ∼31 nm due to the fluctuation of the laser dose caused by different contour geometries. The achieved surface roughness is, nevertheless, in line with previous studies; Malinauskas et al have reported a roughness of ∼30 nm ±3 nm for sol−gel photopolymer SZ2080, 61 and Takada et al found a roughness of 4 to 11 nm for urethane acrylate resin SCR500. 62 It has been suggested that the higher surface roughness resulting in an increase of the surface area can promote the attachment of glioblastoma cells.…”
Section: Discussionsupporting
confidence: 91%
“…It is worth noting that photopolymerized photonic crystal templates or microlenses can be used for imaging inside liquids, since the phase delay of light introduced by the 3D polymeric structure alters the phase of the passing light. As a result, imaging the out-of-focus plane is possible using a 3D photonic crystal template [35].…”
Section: Single Optical Elements: Aspherical Fresnel and Solid Immers...mentioning
confidence: 99%
“…The result suggests that the secondary nanostructures of the FFS-NP are of the functions of 3D diffraction gratings, which may be very useful for the correction of optical aberration and special imaginations of optical systems [28,29]. From the viewpoint of optics design, the surface can be regarded as an element comprising refractive/reflective freeform and high-frequency diffractive structures, constructing the hybrid micro-optics for function integration of the optical component [5,30]. (d) Compared with FTS/STS, the EFCS system made the generation of secondary nanostructures free from the dependence on mechatronic system dynamics.…”
Section: F-theta Freeform Surface With Nano-pyramidsmentioning
confidence: 95%
“…For instance, the nanostructures on the micro-lens array make the array not only suitable for optical imaging but also for antireflective and hydrophobicity applications [4], and the phase gratings on freeform optics can construct the hybrid micro-optics comprising refractive/reflective freeform and high-frequency diffractive structures for function integration of the optical system [5]. To popularize practical applications of the bio-inspired surfaces, a variety of machining methods have been developed which can be classified, according to structure formation modality, into additive and subtractive processes.…”
Section: Introductionmentioning
confidence: 99%